Odpowiedzi

2009-12-02T21:28:52+01:00
A)
4x + 2y = 6 | ×(-3)
9x + 3y = 6 | × 2
-12x -6y = - 18
18x + 6y = 12
6x= -6
x = -1
4×(-1) + 2y = 6
2y = 6+4
y=5


b)
6x - 2y = -2
2x - y = 4
-y =4-2x | ÷ (-1)
y = -4 +2x

6x - 2 * (-4 +2x) = -2
6x +8 -4x = -2
2x = -10
x = -5
y = -4 + 2 *(-5)
y= -14
Najlepsza Odpowiedź!
2009-12-02T21:29:39+01:00
A)
4x + 2y = 6
9x + 3y = 6

4x + 2y = 6
3y=6-9x

4x + 2y = 6
y=2-3x

4x + 2(2-3x) = 6
y=2-3x

4x+4-6x=6
y=2-3x

-2x=6-4
y=2-3x

-2x=2
y=2-3x

x=-1
y=5
-----------------------
b)
6x - 2y = -2
2x - y = 4

6x - 2y = -2
-y=-2x+4 /*(-1)

6x - 2y = -2
y=2x-4

6x - 2(2x-4) = -2
y=2x-4

6x-4x+8=-2
y=2x-4

2x=-10
y=2x-4

x=-5
y=-14